The Paranormal Surrounds Us: Psychic Phenomena in Literature, Culture, and Psychoanalysis by Richard Reichbart - Carpenter, James (Journal of Scientific Exploration, 2020)
The Paranormal Surrounds Us is a tied-together collection of essays by Richard Reichbart, a practicing psychoanalyst whose several strong interests and lifelong love for the mystery of psi, and sense of adventure and ethical sensibility, give the collection several points of focus. In addition to his current analytic practice of many decades, he has also been a student of literature, a playwright, a Yale-trained attorney, and an activist for Native American and African American rights. The book is as scattered as he has been, but it is so full of insights and pleasing prose, that it doesn’t lose much for that. In this time when we prefer our intellectual material in bite-sized chunks, like sparky TED Talks and internet articles, this may feel especially friendly to many. If there is an implicit, underlying focus to the work, it may be implicitly biographical: one curious man’s study of, to paraphrase Freud, the vicissitudes of psi – its expression in our finest literature, in our private and shared unconscious processes, in our different subcultures, in the deepest privacy of intensive psychotherapy, and in the legal and cultural presumptions that implicitly structure our thinking and behavior. There are three main sections to the book: Psi Phenomena in Western Literature, Psi Phenomena and Psychoanalysis, and Psi Phenomena and Culture.